Analysis of the Implementation of Academic Supervision during the Covid-19 Teaching-Learning Process Activities at North Sumatra State SLB - Cawir Rufinus Purba; Nathanael Sitanggang; Wildansyah Lubis; Rosnelli Rosnelli (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
During the COVID-19 pandemic, the learning process using a virtual application that is adjusted to Permendikbud Number 19 of 2020 must be followed by various schools throughout Indonesia, including SLB Negeri Sumatera Utara. During a pandemic that requires policies from school principals to be able to understand and overcome learning conditions according to Permendikbud Number 19 of 2020 whose learning conditions virtually make children with special needs less able to be guided because of the limitations that exist in them, so that teachers as teaching staff are somewhat difficult to apply the learning model that should be done, Where the learning model applied must create the latest innovations and curriculum changes in accordance with conditions and situations. With the application of changes in learning models, students with special needs feel that the lessons given by the teacher make them unable to translate well what the teacher conveys, thus affecting student motivation to learn. The data collection technique carried out is by using interview methods and documentation studies. This research method is a literature research method. The results of the study concluded that SLB Negeri Sumatera Utara has obstacles in the virtual learning process during the Covid-19 period, as stipulated by Permendikbud Number 19 of 2020, where the application of learning models, as well as the tools used to help students understand learning using virtual applications has not been fully maximized, So supervision of teachers and tools used is needed, where this supervision is carried out to ensure whether the existing teachers are competent or in accordance with their bidnag, and supervision of tools used to help students understand virtual learning is done so that the tools used can facilitate the teaching and learning process properly.